Performance analysis of code division multiplexing communication under evaporation duct environment - Liu, Wenjing; Liu, Xiqing; Yan, Shi; Zhao, Linglan; Peng, Mugen (Frontiers in signal processing (Lausanne), 2022)
The evaporation duct is an effective means for realizing non-line-of-sight (NLOS) wireless transmission over the sea. However, the effects of marine weather conditions on electromagnetic propagation have rarely been studied. In this study, the influence of the marine atmospheric environment on electromagnetic propagation was analyzed through numerical simulation. Additionally, the impacts of antenna height, transmission distance, and electromagnetic wave frequency on path loss were studied. Finally, the link capacity of the code division multiplexing (CDM) communication system in the evaporation duct environment was studied via numerical analysis and simulations. Simulation results demonstrated that CDM communication technology can improve the link capacity under an evaporation duct compared with that of the spread-spectrum communication technology.